Figure S2. Cardiovascular hemodynamic responses to EX and MMA in isometric handgrip force-matched males and females - Corey Tomczak (22648301) (2025)
Five males [MVC 12 (3) kg, range 8-15 kg] and 5 females [MVC 11 (3) kg, range 8-15 kg, P = 0.774] were matched for isometric handgrip force. Individual data and group mean (SD) for males and females at rest, EX, and MMA in isometric handgrip force-matched SBP (A), LV wall stress (D), and TPR (E) analyzed by 2 (sex) × 3 (condition) repeated measures ANOVA with Holm-Sidak post hoc multiple comparisons. Isometric handgrip force-matched SBP, LV wall stress, and TPR responses to EX (ΔEX-Rest; B, E, H) and MMA (ΔMMA-Rest; C, F, I), respectively, are compared between males (closed circles) and females (open circles) using independent samples t-tests. * P < 0.05 vs. males within condition; ‡ P < 0.05 vs. rest in both sexes; EX, 30% MVC isometric handgrip exercise; LV, left ventricular; MMA, muscle metaboreflex activation by post-exercise circulatory occlusion; SBP, systolic blood pressure; TPR; total peripheral resistance.